Understanding production and safety situations of organic food in Thailand - Thararat Chitov (2020)
© Springer Nature Singapore Pte Ltd. 2020. The rising demand for safe food in Thailand has led to the increasing popularity of organic food. This calls for a significant transition from conventional agriculture, in which agricultural chemicals are employed to protect plants and animals and to enhance yields of agricultural produce, to organic agriculture. Such transition, however, is a complex process that requires farmers’ commitment, support from governmental and non-governmental organisations through the production chain and marketing, and supportive national policy and regulations. This chapter presents on how organic food in Thailand is produced, and addresses issues related to food production and safety that organic farmers and organic food manufacturers are facing or can anticipate. Management of organic production, using both traditional knowledge and modern technology, and how they can affect food safety, are discussed. It also raises key issues about existing regulatory systems and mechanisms that can support organic agriculture and organic food safety control measures in the Thai context.